Formula Sheet - Midterm 3, 2202A

# Formula Sheet - Midterm 3, 2202A - FORMULAE SHEET FINAL...

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: FORMULAE SHEET FINAL EXAM : ECON 2202 x1 - x 2 1 = + 2 n1 n2 2 2 2 d= 2 d i=1 n i n n where di = x1i - x 2i (x 1 - x2 z / 2 ) 1 + 2 n1 n2 z= (x 1 - x 2 - ( 1 - 2 ) 1 + 2 n1 n2 2 2 ) (d - d ) i i=1 2 d = n-1 n (d - d) i i =1 n 2 x1 - x 2 = s p 1 1 + n1 n 2 d t /2 t= d - d n -1 n sp = ( n1 - 1) s12 + ( n 2 - 1) s 2 2 n1 + n 2 - 2 (d i=1 n i - d) 2 ( x1 - x 2 ) t /2 sp t= 1 1 + n1 n 2 n -1 n (x 1 - x 2 - ( 1 - 2 ) 1 1 + n1 n 2 ) p1 -p2 sp 2 2 p1(1 - p1 ) p 2 (1 - p 2 ) + n1 n2 z / 2 p1 (1 - p1 ) p 2 (1 - p 2 ) + n1 n2 x1 - x 2 = 2 s1 s (s1 /n1 + s 2 /n 2 ) 2 2 + 2 and df = 2 2 n1 n2 (s1 /n1 ) (s 2 /n 2 ) 2 2 n -1 + n -1 2 1 ( p1 - p 2 ) z= ( p1 - p 2 ) - ( 1 - 2 ) (x 1 - x2 t ) /2,df = 2 (s1 /n1 + s2 /n2 )2 2 2 (s1 /n1 )2 (s2 /n2 )2 + 2 n -1 n 2 -1 1 2 s1 s 2 + 2 n1 n2 1 1 p(1 - p) + n n 1 2 n p + n 2p 2 x + x2 where p = 1 1 = 1 n1 + n 2 n1 + n 2 t= (x 1 - x 2 - ( 1 - 2 ) 2 s1 s 2 + 2 n1 n 2 ) and df = 2 (s1 /n1 + s 2 /n 2 ) 2 2 2 (s1 /n1 ) 2 (s 2 /n 2 ) 2 2 n -1 + n -1 2 1 2 = (n - 1)s 2 2 SST = SS A + SSB + SS AB + SSE MS AB MSE MS A MSE (n - 1)s2 (n - 1)s2 2 2 2 U L s s 2 1 2 2 F= F= F= Fmax 2 s max = 2 s min F= MS B MSE SST = SSB + SSW F= MSB MSW MSW 1 1 + 2 ni n j 2 = (oi - ei )2 ei (oij - eij )2 eij Critical Range = q 2 = i=1 j =1 r c SST = SSBL + SSB + SSW F= MSBL MSW MSB MSW 2 b (i thRow Total)(j th Column Total) e ij = Total Sample Size F= LSD = t /2,(k -1)(b-1) MSW CONTINUED r= ( x - x)( y - y) [ ( x - x ) ][ ( y - y ) 2 2 = [n( x 2 ) - ( x ) 2 ][n( y 2 ) - ( y ) 2 ] n xy - x y t= r 1- r 2 n-2 sb1 = (x - x) s 2 = s x2 - ( x)2 n b1 = ( x - x )( y - y ) = ( x - x) x 2 x y xy - 2 t= - n ( x )2 n b1 - 1 s b1 b 1 t /2 s b1 b 0 = y - b1x ^ y t /2 s 2 1 (x p - x) + n (x - x)2 SST = ( y - y ) 2 ^ SSE = ( y - y ) 2 ^ SSR = ( y - y ) 2 SST = SSR + SSE ^ y t /2 s 2 1 (x p - x) 1+ + n (x - x)2 n -1 R 2 = 1 - (1 - R 2 ) A n - k - 1 SSR MSR k F= = SSE MSE n - k -1 2 2 SSR R = = SST 2 ^ (y - y) (y - y) t= bi - 0 sbi 1 1 - R2 j SSE s = = n - k -1 ^ ( y - y) 2 VIFj = n - k -1 b i t / 2 sbi ...
View Full Document

{[ snackBarMessage ]}

Ask a homework question - tutors are online